The antiferroelectric phase transition in Rb3D(SO4)2 single crystals studied by 87Rb NMR - Böhmer, Roland; Titze, A.; Hinze, G. (The American Physical Society, 1998)
The quadrupole perturbed central transition of the magnetic 87Rb resonance was used to study Rb3D(SO4)2 single crystals. Three resonance lines were found at room temperature. This result is in accord with the monoclinic space group reported for these crystals and does not require the previously invoked self-trapped proton states. The number of resonance lines quadruples below the antiferroelectric phase transition near 82 K. From the line splitting the order-parameter exponent of the low-temperature phase was found to be β=0.2. Spin-lattice relaxation times have been determined in the fully protonated and deuterated disulfates and were used to deduce the temperature dependence of the order-parameter fluctuations.
Keywords: 530